Students’ Perception about Status of Bedside Teaching in Undergraduate Medical Education of Bangladesh - Sultana, Jobaida; Ara, Iffat; Talukder, Md Humayun Kabir; Khan, Md Manir Hossain; Sultana, Mahmuda; Munira, Serajoom (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Introduction: Bedside teaching is the core teaching strategy in the clinical study in undergraduate medical education of Bangladesh. Many of the environments and opportunities available for bedside teaching and learning have changed. Students’ views about current status of bed side teaching in Obstetrics and Gynaecology was studied in this study. Methodology: This was a cross sectional study conducted in seven (three public and four private) medical colleges in Bangladesh from July 2012 to June 2013. A total 578, 5th year MBBS students were enrolled who have completed at least 15 days of bedside teaching in Obstetrics and Gynaecology department. A self-administered structured questionnaire (Annex 1) with a five point Likert scale (1- strongly disagree, 5-strongly agree) was used for obtaining information from the students. The questionnaire had four main sections- physical environment of bedside sessions, issues regarding patient’s comfort and attitude towards patient, teaching tasks, group dynamics and there was a space to write any other comments. Each section had a number of items and total 25 items were observed. For each variable frequency distribution, mean score and standard deviation (SD) were calculated. Here mean score 5- no need of further improvement, as it covered all the required criteria, 4 to <5- very minimum effort, 3 to <4- some effort, 2 to <3= moderate effort, 1to <2= considerable efforts are needed to fulfill the required criteria. Result: The overall mean score on physical environment factors was 2.75(.44), issues regarding patient’s comfort and attitude toward patient was 3.74(.48), teaching tasks was 3.12(.45) and group dynamics was 3.08(.21). Conclusion: In all aspects of bed side teaching minimum to moderate efforts are necessary to make it more effective. The administrators and teachers should ensure comfortable physical environment in bedside teaching and must learn how to involve patients and learners in the educational process. So along with training on general principles of teaching, the clinical teachers should be provided with special training on bedside teaching skills. J Bangladesh Coll Phys Surg 2017; 35(4): 163-169